Performance Evaluation of Molecularly Imprinted Polymer using Propanol as Porogen for Atenolol Recognition in Human Serum - Meilia Suherman; Ike Susanti; Driyanti Rahayu; Rimadani Pratiwi; Aliya Nur Hasanah (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Atenolol is a cardiovascular drug that has a narrow therapeutic index with long-term use and it’s often used as doping. Atenolol has a small concentration in human boby and it’s in  biological matrix (serum) so in the testing need a selective extraction so  the analyte can be pra-concentration and removed from matrix. Two molecularly imprinted polymers (MIPs) on propanol as porogen  have been made with two different methods i.e. bulk polymerization and precipitation polymerization. The polymer was made using atenolol as a template, methacrylic acid as a functional monomer, and ethylene glycol dimethacrylate as a crosslinker. Prformance evaluations showed that polymers from bulk polymerization provide better performance than polymers from precipitation polymerization when tested against standard solution. However, this sorbent has low  recovery percentage after applied into serum sample and could not be used as alternative for atenolol extraction in human serum.Key words: Molecularly imprinted polymer, Atenolol, Solid Phase Extraction, Preparation  method, propanol.